Analisis Implementasi Kemitraan Bank Sampah Dan Dinas Lingkungan Hidup Dalam Pengelolaan Sampah Di Kota Jambi - Fauzi, Gian; Pahlefi, Pahlefi; Windarto, Windarto (Zaaken: Journal of Civil and Business Law, 2025)
This research aims to identify and analyze the implementation of partnership between waste banks and the Environmental Agency of Jambi City in waste management and to analyze the constraints in implementing the partnership between waste banks and the Environmental Agency in waste management. The type of research used in this study is juridical empirical with data collection methods in the form of interviews and direct field observations. From the research results, it is known that 1). The implementation of the partnership between the Environmental Agency and the Main Waste Bank of Jambi City was formed through an official appointment in the Decree of the Head of the Environmental Agency of Jambi City Number 161 of 2020 2). The main constraints in running the partnership are due to the independent nature of the Waste Bank and the lack of human resources provided by the Environmental Agency.